Pengembangan Aplikasi Perangkat Bergerak Berbasis Android Untuk Layanan Masyarakat Dengan Metode Mobile-D (Studi Kasus : RSUD Ngudi Waluyo Wlingi Kabupaten Blitar) - Jerry Kurnia Sandy; Agi Putra Kharisma; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In Blitar Regency there is one public hospital in Wlingi District as a place of health services for the community, namely the Hospital of Ngudi Waluyo Wlingi Hospital. The system so far has implemented patient registration services, but still uses a manual system, in the morning patients must come first to pick up the queue number, wait around the counter and pay attention to queue information through the monitor, so that the system is less effective. The problems in the hospital at the Ngudi Waluyo Wlingi Hospital were developed by the Android-based Mobile Application for community services with the main features of new patient registration, patient registration and patient queues, with additional features of several information systems related to the Ngudi Waluyo Wlingi Hospital. The method in developing this application uses Mobile-D which requires an iterative needs analysis process, then implemented with java language programming, and uses the help of IDE Android Studio. The design process in this application was obtained twelve functional requirements as users, four requirements as admin and two non-functional requirements. Application testing is done, namely testing validation, compatibility, and usability. The results of the tests carried out obtained valid status with sixteen functional, easy to use with a SUS 72.33 score, and compatible running on several Android devices.